Fostering inclusivity in education - Karin Milles (Nordisk Tidskrift för Socioonomastik)
The article delves into the critical issue of integrating pronoun awareness in Swedish educational settings to cultivate more inclusive environments. Through a mixture of surveys and interviews, the research examines teachers’ experiences and attitudes towards pupils who identify with new pronouns, illuminating the challenges that educators may encounter and assessing the extent to which schools are equipped to support transgender pupils. The findings indicate that while many educators recognize the importance of using the pronouns pupils identify with, recognizing it as a vital component of an inclusive educational approach, there is also resistance within the teaching profession. The study also uncovers significant obstacles stemming from school culture and administrative frameworks that hinder transgender pupils from fully expressing and developing their identities alongside their peers. Based on these insights, the article proposes actionable recommendations for school leaders, aimed at enhancing support systems and develop policies that better accommodate the needs of transgender pupils and foster a truly inclusive educational environment.